2003
DOI: 10.1159/000075111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study for Alleviating Opiate Drug Psychological Dependence by a Method of Ablating the Nucleus accumbens with Stereotactic Surgery

Abstract: The aim of this study was to explore a new way of treating drug addiction by ablating the nucleus accumbens (NAC), which has a close relationship with drug-induced psychological dependence, using stereotactic surgery, blocking the mesocorticolimbic dopamine circuit, alleviating craving for drugs and lowering the relapse rate after detoxification. On the basis of animal experiments, stereotactic surgery was performed in 28 patients by making a lesion in the NAC bilaterally to treat opiate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 2 publications
2
82
1
6
Order By: Relevance
“…By November 2004, this operation had been performed on a total of 272 opiate addicts, and short-term follow-ups revealed satisfactory results [7,8] . However, this treatment was halted due to ethical problems associated with irreversible damage to the brain structure and the lack of long-term follow-up data.…”
Section: Introductionmentioning
confidence: 99%
“…By November 2004, this operation had been performed on a total of 272 opiate addicts, and short-term follow-ups revealed satisfactory results [7,8] . However, this treatment was halted due to ethical problems associated with irreversible damage to the brain structure and the lack of long-term follow-up data.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now largely accepted that interfering with the DA system affects motivation in general. Other surgical targets such as the nucleus accumbens (8) or the cortex (9) have been tested in animals or in opiates addicts (10) with no convincing results so far.…”
mentioning
confidence: 99%
“…In 2003, Gao et al 12 reported on ablation of the nucleus accumbens to treat addiction, based on several animal experiments and recent studies that had revealed the relationship between psychological dependence induced by drug addiction and the mesocorticolimbic dopamine circuit. Ablation of the nucleus accumbens would lead to blockage of the mesocorticolimbic dopamine circuit.…”
Section: Ablation Of the Nucleus Accumbensmentioning
confidence: 99%